Možnosti za uporabo posplošene tržne vrednosti nepremičnin - Pšunder, Igor (Geodetski vestnik, 2013)
Generalized real estate market value was evaluated by the Surveying and Mapping Authority of the Republic of Slovenia in 2010. Evaluations were made for all real estate in Slovenia and communicated to the real estate owners; this caused much controversy. Later, owners corrected or changed 1,153,909 pieces of real estate data. The distrust of generalized real estate market value was intensified by the media's negative attitude towards it, expressed in the majority of articles. When the period for making changes and corrigenda expired, an impression was established of a satisfactory and precise valuation of real estate. Even the banks started using generalized real estate market value as referential information in smaller real estate transactions for the banks' mortgage lending needs. Nevertheless, the professional public has expressed concerns about the appropriateness of using generalized market value for purposes other than imposing taxes, since some specific characteristics of real estate (e.g. the view) are ignored. Furthermore, the information about generalized market value is conveyed with atime delay - it can thus be not only obsolete but also misleading in unstable market conditions. This article discusses perceptions of generalized market value. It is based on research that was conducted among professionals and the general public in Slovenia. The results show that professionals and the general public have adopted generalized market value relatively well. Furthermore, 60% of the professional public thinks that generalized market value could also be used for other purposes (not only for imposing taxes).
Keywords: nepremičnine; Slovenia; Slovenija; tržna vrednost; uporaba; vrednotenje